2001
DOI: 10.1046/j.1537-2995.2001.41101249.x
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter evaluation of PCR methods fordetecting CMV DNA in blood donors

Abstract: Seven CMV PCR assays currently used for research and/or diagnostic applications displayed marked variations in sensitivity, specificity, and reproducibility when applied to coded analytical and clinical control samples containing cellular DNA from the equivalent of 250,000 WBCs. These results will be useful in the selection of assays with performance characteristics appropriate to donor screening objectives. They may also help explain discrepant findings from previous studies that used PCR to determine CMV DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
77
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(84 citation statements)
references
References 33 publications
5
77
2
Order By: Relevance
“…Indeed, we previously showed that 36% of HCMV IgG-negative blood donors with HCMV DNA-positive blood cells were IgG positive in an ELISA that uses a clinical isolate as antigen. 19 Similarly, in the present study, serum from 5 (42%) of 12 patients that were HCMV IgG negative according to three serology tests utilizing AD169-derived antigens, were IgG positive in an ELISA assay using antigens from a clinical isolate. Nevertheless, 9 (58%) of 12 patients were still HCMV IgG negative, although their tumors were positive for HCMV by immunohistochemistry with two different HCMV-specific antibodies, HCMV DNA were detected in their blood cells, and a majority of them had T cells that responded to HCMV peptides.…”
Section: E982391-4 Volume 4 Issue 2 Oncoimmunologysupporting
confidence: 72%
See 2 more Smart Citations
“…Indeed, we previously showed that 36% of HCMV IgG-negative blood donors with HCMV DNA-positive blood cells were IgG positive in an ELISA that uses a clinical isolate as antigen. 19 Similarly, in the present study, serum from 5 (42%) of 12 patients that were HCMV IgG negative according to three serology tests utilizing AD169-derived antigens, were IgG positive in an ELISA assay using antigens from a clinical isolate. Nevertheless, 9 (58%) of 12 patients were still HCMV IgG negative, although their tumors were positive for HCMV by immunohistochemistry with two different HCMV-specific antibodies, HCMV DNA were detected in their blood cells, and a majority of them had T cells that responded to HCMV peptides.…”
Section: E982391-4 Volume 4 Issue 2 Oncoimmunologysupporting
confidence: 72%
“…Such analyses have for obvious reasons not been done on tissues samples from healthy individuals, but a discrepancy between HCMV serology data and HCMV DNA detection in blood has been reported as discussed above. 17,18,19 Thus, several lines of evidence suggest that HCMV carriers are not always defined by serology, and our findings imply that this is frequently the case in GBM patients. We observed that 29% of GBM patients positive for HCMV DNA in blood cells and HCMV proteins in the tumor, were negative for HCMV IgG by serology, but 85% of them had T-cells that were reactive against HCMV IE and/or pp65 peptides.…”
Section: E982391-4 Volume 4 Issue 2 Oncoimmunologysupporting
confidence: 55%
See 1 more Smart Citation
“…17 However, it should be noted that CMV genome have been detected in clinical samples of CMV-seronegative, healthy blood donors. 52 Larsson et al even detected the CMV genome in 55% of peripheral leukocytes of CMV-seronegative blood donors. 53 The presence of the CMV genome in samples of CMV-seronegative individuals, however, could not be confirmed by other large studies.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the molecular detection of CMV DNA is essential for the diagnosis of acute CMV and the assessment of disease progression through monitoring of active CMV infections (virus clearance versus persistence). Early studies using different PCR assays, mainly inhouse tests, revealed considerable differences in their sensitivities and specificities, confirming the need for implementation of validated CMV assays (15). Therefore, the performance of different commercially available amplification systems was evaluated.…”
Section: Discussionmentioning
confidence: 99%